Polityka spójności na poziomie lokalnym - doświadczenia Wielkiej Brytanii - Kenc, Joanna (Policy at the Local level - Great Britain's Experience, 2008)
The differences between countries in social and economic level of development appearing in the progressive process of the European Integration very often become the aim of scientific research. Diversities mainly apply to countries which joined the European Union in 2004 and the EU with 15 member states. Great Britain is one of countries next to France, Finland and Italy where the difference between the richest and the poorest region is the most visible. This article shows the analysis of British national programme introduced by government in 2001 which aim is to narrow the gap between deprived areas and the rest of the country. Neighbourhood Renewal Programme was originally addressed to 88 districts representing 10% of the most deprived areas in the country. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 217-226